A comparison of U.S. infant feeding policy changes to Global Breastfeeding Collective policy priorities - Harrigan, Paige B.; Schenk, Todd; Volpe, Stella L.; Hedrick, Valisa E.; Khan, Tuba; Misyak, Sarah A. (Frontiers in Public Health, 2025)
IntroductionPublic policy plays an important role in shaping how infants are fed. The Global Breastfeeding Collective (GBC) provides a set of policy priorities for countries to promote, protect and support breastfeeding. The GBC uses scorecards to document progress toward meeting those priorities. The purpose of this study was to assess recent United States (U.S.) federal infant feeding policy changes against the GBC's policy priorities to identify areas of alignment and gaps for policies supporting optimal infant feeding.MethodsChanges in U.S. federal infant feeding legislation, regulation, and presidential documents between 2014 and 2023 were compared with and coded into GBC priority categories. Policy changes not aligned with GBC priorities were coded into additional non-GBC topic categories that were developed inductively.ResultsFifty-seven federal infant feeding policies were adopted or substantively modified within the study period. Of these, only 17 aligned with at least one of the GBC policy priorities. Forty-nine policies included changes that did not match GBC policy priorities. Policy changes that did not align with GBC priorities addressed infant formula manufacturing, lactation spaces, and breastfeeding supplies, among other topics.ConclusionAlthough most recent federal infant feeding policy changes in the U.S. did not align with the breastfeeding policy priorities established by the GBC, opportunities to promote and protect breastfeeding were identified. Some U.S. breastfeeding policy changes outside of GBC priorities have potential to strengthen breastfeeding.